2021
DOI: 10.2147/imcrj.s327196
|View full text |Cite
|
Sign up to set email alerts
|

Large Vessel Occlusion Causing Cerebral Ischemic Stroke in Previously Healthy Middle-Aged Recently Recovered from Severe COVID-19 Infection

Abstract: Background Severe acute respiratory syndrome coronavirus (SARS-CoV-2) due to novel coronavirus disease 2019 (COVID-19) has led to an unprecedented worldwide pandemic with diverse respiratory symptoms as well as systemic manifestations and complications. The neurological manifestations of COVID-19 include, but are not limited to, headache, cerebrovascular disease, and skeletal muscle injury. Case Report Herein, we present a case of stroke with large vessel occlusion in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…O SARS-CoV-2, é conhecido usualmente por causar sintomas respiratórios, podendo evoluir para a SDRA até à falência de múltiplos órgãos, bem como, acometer o sistema nervoso central 30 . Existem diversos relatos na literatura que sugerem uma associação entre a infecção pela COVID-19 e a ocorrência de complicações tromboembólicas 16 , cursando com a ativação sistêmica da cascata de coagulação e tendo os três componentes da tríade de Virchow (estase sanguínea, hipercoagulabilidade e lesão endotelial) como a base da trombose, especialmente naqueles com a forma grave da doença 31 Apesar de os pacientes mais suscetíveis a sofrerem AVEi secundário à infecção pelo SARS-CoV-2 apresentarem comorbidades, o relato de caso de Alashim et al 16 Quanto à incidência de AVEi em pacientes infectados pelo SARS-CoV-2, no estudo de Stamm et al 9 foi de 1-2%. Já na revisão sistemática de Tan et al 29 , o valor encontrado foi de 1,2%.…”
Section: Discussão Dos Dadosunclassified
“…O SARS-CoV-2, é conhecido usualmente por causar sintomas respiratórios, podendo evoluir para a SDRA até à falência de múltiplos órgãos, bem como, acometer o sistema nervoso central 30 . Existem diversos relatos na literatura que sugerem uma associação entre a infecção pela COVID-19 e a ocorrência de complicações tromboembólicas 16 , cursando com a ativação sistêmica da cascata de coagulação e tendo os três componentes da tríade de Virchow (estase sanguínea, hipercoagulabilidade e lesão endotelial) como a base da trombose, especialmente naqueles com a forma grave da doença 31 Apesar de os pacientes mais suscetíveis a sofrerem AVEi secundário à infecção pelo SARS-CoV-2 apresentarem comorbidades, o relato de caso de Alashim et al 16 Quanto à incidência de AVEi em pacientes infectados pelo SARS-CoV-2, no estudo de Stamm et al 9 foi de 1-2%. Já na revisão sistemática de Tan et al 29 , o valor encontrado foi de 1,2%.…”
Section: Discussão Dos Dadosunclassified
“…The study by Misra et al 5) , which included 350 studies, providing data from 145,721 patients with COVID-19, found that one in 50 patients experienced a stroke. In particular, the increase in cases of large vessel occlusion (LVO) in patients with COVID-19 6) is noteworthy due to the increased risk of mortality and worst sixth-month good outcome (modified Rankin Scale score ≤ 2) that they present 7) .We conducted a systematic review and meta-analysis to assess the influence of COVID 19 on clinical outcomes and treatment success in patients with stroke due to occlusion of large vessels.…”
Section: Introductionmentioning
confidence: 99%